Nilai vertebrae heart size anjing kintamani bali pada usia berbeda - I Putu Gede Yudhi Arjentinia; Putu Ayu Sisyawati Putriningsih (ARSHI Veterinary Letters, 2018)
Anatomical physiological clinical studies such as cardiac image, is one of the important studies that must to strengthen the position of kintamani bali dog as a dog recognized by the FCI. Cardiac image that can be seen is the size of the cardiac based on the value of vertebral heart size (VHS). The results obtained are used as the standard size and assessment of cardiac of kintamani bali dogs. This study aims to determine the VHS value of kintamani bali dog based on age group 12 and 24 months. The sample used 40 kintamani bali dogs, such as 20 dogs of 12 months and 20 dogs of 24 months. Images were taken by X-ray to determine the value of VHS kintamani bali dogs. The method used a lateral thoracic radiograph. Measured by using calipers at the longest axis from cardiac silhouette from carina to the apex, and the short axis were measured from the widest part of the cardiac silhouette. Then transfer that measured to the vertebrae, starting at the cranial edge of T4, count the number of vertebrae that fall within the caliper points, and sum of the two measurements. The result showed that the values of VHS at 12 months kintamani dogs were 9.4v±1.6 and the 24 month were 9.4v±0.8